A high-density BAC physical map covering the entire MHC region of addax antelope genome - Chaokun Li; Longxin Chen; Xuefeng Liu; Xiaoqian Shi; Yu Guo; Rui Huang; Fangyuan Nie; Changming Zheng; Chenglin Zhang; Runlin Z. Ma (BMC Genomics, 2019)
Abstract Background The mammalian major histocompatibility complex (MHC) harbours clusters of genes associated with the immunological defence of animals against infectious pathogens. At present, no complete MHC physical map is available for any of the wild ruminant species in the world. Results The high-density physical map is composed of two contigs of 47 overlapping bacterial artificial chromosome (BAC) clones, with an average of 115 Kb for each BAC, covering the entire addax MHC genome. The first contig has 40 overlapping BAC clones covering an approximately 2.9 Mb region of MHC class I, class III, and class IIa, and the second contig has 7 BAC clones covering an approximately 500 Kb genomic region that harbours MHC class IIb. The relative position of each BAC corresponding to the MHC sequence was determined by comparative mapping using PCR screening of the BAC library of 192,000 clones, and the order of BACs was determined by DNA fingerprinting. The overlaps of neighboring BACs were cross-verified by both BAC-end sequencing and co-amplification of identical PCR fragments within the overlapped region, with their identities further confirmed by DNA sequencing. Conclusions We report here the successful construction of a high-quality physical map for the addax MHC region using BACs and comparative mapping. The addax MHC physical map we constructed showed one gap of approximately 18 Mb formed by an ancient autosomal inversion that divided the MHC class II into IIa and IIb. The autosomal inversion provides compelling evidence that the MHC organizations in all of the ruminant species are relatively conserved.